The Enigma of Heat Shock Proteins in Immune Tolerance - van Eden, Willem; Jansen, Manon A. A.; Ludwig, Irene; van Kooten, Peter; van der Zee, Ruurd; Broere, Femke (Frontiers in Immunology, 2017)
The fundamental problem of autoimmune diseases is the failure of the immune system to down-regulate its own potentially dangerous cells, which leads to destruction of tissue expressing the relevant auto-antigens. Current immunosuppressive therapies offer relief but fail to restore the basic condition of self-tolerance. They do not induce long-term physiological regulation resulting in medication-free disease remissions. Heat shock proteins (HSPs) have shown to possess the capacity of inducing lasting protective immune responses in models of experimental autoimmune diseases. Especially mycobacterial HSP60 and HSP70 were shown to induce disease inhibitory IL-10 producing regulatory T cells (Treg) in many different models. This in itself may seem enigmatic, since based on earlier studies, HSP were also coined sometimes as pro-inflammatory Damage Associated Molecular Patterns (DAMPS). First clinical trials with HSPs in rheumatoid arthritis and type I diabetes have also indicated their potential to restore tolerance in autoimmune diseases. Data obtained from the models have suggested three aspects of HSP as being critical for this tolerance promoting potential: 1. Evolutionary conservation, 2. Most frequent cytosolic/nuclear MHC class II natural ligand source, and 3. Upregulation under (inflammatory) stress. The combination of these three aspects, which are each relatively unique for HSP, may provide an explanation for the enigmatic immune tolerance promoting potential of HSP.